JDHOR 2021
DOI: 10.46889/jdhor.2021.2103
|View full text |Cite
|
Sign up to set email alerts
|

Dental Shade Matching: Recent Technologies and Future Smart Applications

Abstract: Shade matching in dental practice has been a great challenge for years. Shade matching has been carried out visually which proved unreliable and subjective. Alternatively, digital devices as spectrophotometer, colorimeter and digital photography were introduced which proved reliable but increased cost and time. The combination of patients requesting more esthetic restorations with dentists not willing to invest in expensive solutions, motivated researchers to investigate in new technologies for cost effective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…(Pearson's alpha =.05) Colour matching across multiple shade guidelines has proven to be a tough process with inconsistent outcomes. [16,17] The null hypothesis was disproved when it was found that all VITAcoded shade guides showed variations in hue, chroma, and value when compared to the VITA Classical control. The use of colorimeters, spectrophotometers, digital cameras, and a combination of these tools has advanced shade matching.…”
Section: Resultsmentioning
confidence: 99%
“…(Pearson's alpha =.05) Colour matching across multiple shade guidelines has proven to be a tough process with inconsistent outcomes. [16,17] The null hypothesis was disproved when it was found that all VITAcoded shade guides showed variations in hue, chroma, and value when compared to the VITA Classical control. The use of colorimeters, spectrophotometers, digital cameras, and a combination of these tools has advanced shade matching.…”
Section: Resultsmentioning
confidence: 99%
“…The difference in shade of samples made by different labs was estimated using a digital spectrophotometer and CIE LAB system. The objective analysis of color of metal ceramic restoration by spectrophotometer is not influenced by variations in light source or observer [8,12,13]. The reliability and repeatability of this technique is universally accepted as it aids in precise measurement of color of restoration [13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…The partial difference might be due to smaller sample size of this study, and the partial similarity of this study might be due to the use of instrumental techniques to assess shade matching or use of appropriate aperture size of the colorimeter to reduce the chances of error due to edge loss [4]. The other reasons for differences in results of different studies may be attributed to factors such as technique sensitivity of porcelain application, changes due to different number of firing cycles, glazing, thickness of porcelain in crowns, or use of different modes for assessment of shade, i.e., objective versus subjective analysis [12,18,19]. The differences or similarities may also be due to use of different or similar brands of porcelain or difference in equipment owned by different labs [4].…”
Section: Discussionmentioning
confidence: 99%
“…De otra parte, los espectrofotómetros de uso clínico (Vita EasyShade®, SpectroShade-TMMicro® y CrystalEye) y los colorímetros (Shade eye-NCC®) han demostrado ser confiables, con una buena reproducibilidad y repetibilidad al evaluar el color dental; es decir, obtienen mejores resultados en la determinación del color en comparación con el método visual (13,21,(31)(32)(33). Los espectrofotómetros son los más utilizados en la práctica odontológica, puesto que permiten igualar y reproducir en gran proporción el color dental debido a su configuración de iluminación y de medición.…”
Section: Instrumentosunclassified
“…Acta Odontológica Colombiana Julio -Diciembre 2022; 12(2): 61 -77 uso de programas para su análisis (29,32,34). Los sistemas de imágenes digitales, como la combinación de cámara fotográfica y uso de softwares, permiten la toma de color sin contacto con la muestra y demuestran ser innovadores.…”
Section: Research Articlesunclassified